New Methylene Blue Covalently Functionalized Graphene Oxide Nanocomposite as Interfacial Material for the Electroanalysis of Hydrogen Peroxide - Chen, Jifang; Gao, Ziqing; Yang, Ruonan; Jiang, Huiling; Bai, Lin; Shao, Ailong; Wu, Hai (Frontiers in Chemistry, 2021)
New methylene blue (NMB), a phenothiazine dye, was covalently bonded to graphene oxide (GO) using glutaraldehyde as a crosslinking agent, which was characterized by spectroscopic techniques and electrochemistry. The obtained GO-NMB nanocomposite was used as interface material to construct a novel electrochemical sensor for the determination of hydrogen peroxide (H2O2). The electrochemical sensor based on GO-NMB nanocomposite exhibited excellent electrocatalytic activity for the reduction of hydrogen peroxide (H2O2), which was also enhanced by GO within GO-NMB nanocomposite. With the optimized experimental conditions, the developed sensor showed high sensitivity (79.4 μA mM-1 cm-2) for electrocatalytic determination of H2O2 at the applied potential of -0.50 V in the concentration range of 0.000333 mM to 2.28 mM. The low limit of detection (1.35 uM), good reproducibility, and high stability of the sensor suggests that the electrochemical sensor based on GO-NMB nanocomposite possesses obvious advantages, which paves a new avenue to functionalize GO for obtaining electrode interface materials.